Efektivitas Bermain Lotto untuk Meningkatkan Konsentrasi Belajar bagi anak ADHD - Sari, Lola Monika; Marlina, Marlina (Jurnal Basicedu, 2021)
This research is based on getting an ADHD child who has difficulty learning concentration, learning concentration in focusing on the material being worked on. This study aims to increase learning concentration for ADHD children at SDN 11 Pauh Padang. This type of research experiments in the form of a single subject (Single Subject Research) with de s ain ABA, the research subject is a child with ADHD, show symptoms of a lack of ability to concentrate full attention to the object. Data collection techniques in this study used a duration to see how long the child was able to focus on the material being worked on within 20 minutes of the learning process. Data analysis techniques using visual graph techniques. The results of this study indicate that playing lotto can increase learning concentration for ADHD children at SDN 11 Pauh Padang seen from the results of data analysis in conditions and between conditions.